The Dynamics of Victory: Exploring the Movement Patterns of Female Brazilian Jiu-Jitsu Athletes in Win-ning and Losing Combats through Time-Motion Analysis - Marco Antonio Ferreira dos Santos; Clovis de Albuquerque Maurício; Dany Alexis Sobarzo Soto; Esteban Aedo-Muñoz; Ciro José Brito; Emanuela Pierantozzi; Bianca Miarka (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2024)
In the quest to understand the dynamics of female Brazilian Jiu-Jitsu (BJJ) combats, this research delves into the world of winning and losing. By comparing time-motion analysis based on different outcomes, our objective was to unveil the movement patterns of victory. Our sample included 209 winning (W) versus 209 losing (L) female international BJJ combats, presenting a comprehensive picture of the combat landscape. Through time-motion analysis, we explored various BJJ combat phases, such as approach, gripping, transition, side control, mounting, attack, defense, low-intensity movement, and total time. The statistical results highlight significant differences between winners and losers in key aspects of the combats. Notably, side control (W= 47.7 [27.8; 96.5]s vs. L= 27.3 [20.3; 41.9]s), mount (W= 40.0 [16.6; 85.9]s vs. L= 15.9 [6.1; 25.6]s), attack (W= 50.1 [28.6; 86.7]s vs. L= 16.6 [7.7; 35.7]s), defense (W= 14.6 [6.6; 38.2]s vs. L= 38.8 [17.7; 77.0]s), and low-intensity movement (W= 55.9 [23.4; 132.2]s vs. L= 111.5 [58.7; 225.6]s) revealed differences between the winners and losers. The implications extend to sports psychology and judo training, providing knowledge for enhancing performance, optimizing training programs, and making strategic decisions during combat.